2017
DOI: 10.1038/ncomms14860
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric cross-talk in chromatin can mediate drug-drug synergy

Abstract: Exploitation of drug–drug synergism and allostery could yield superior therapies by capitalizing on the immensely diverse, but highly specific, potential associated with the biological macromolecular landscape. Here we describe a drug–drug synergy mediated by allosteric cross-talk in chromatin, whereby the binding of one drug alters the activity of the second. We found two unrelated drugs, RAPTA-T and auranofin, that yield a synergistic activity in killing cancer cells, which coincides with a substantially gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
75
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 57 publications
(92 reference statements)
5
75
0
Order By: Relevance
“…firstly found that the RAPTA-T can combine with auranofin to yield a synergistic activity in killing cancer cells via the allosteric cross-talk in chromatin. 172 In addition, the RAPTA derivatives inhibited the activity of glutathione transferase, lysozyme, cathepsin B (Cat B) and TrxR. 173 Thus, RAPTA complexes can readily react with proteins and inhibit enzymes, but there is no significant correlation between this reactivity and toxicity in cancer cells.…”
Section: Arene Ruthenium(ii) Complexesmentioning
confidence: 99%
“…firstly found that the RAPTA-T can combine with auranofin to yield a synergistic activity in killing cancer cells via the allosteric cross-talk in chromatin. 172 In addition, the RAPTA derivatives inhibited the activity of glutathione transferase, lysozyme, cathepsin B (Cat B) and TrxR. 173 Thus, RAPTA complexes can readily react with proteins and inhibit enzymes, but there is no significant correlation between this reactivity and toxicity in cancer cells.…”
Section: Arene Ruthenium(ii) Complexesmentioning
confidence: 99%
“…[77] Further, RAPTA-T has been shown to induce allosteric binding of other drugs in the nucleosome core particle thereby mediating drug-drug synergies. [78] In vivo experiments in the chorioallantoic membrane of the chicken embryo (CAM) and in a CBA mouse model revealed that RAPTA-T reduces the tumor burden of invasive cancer types. [77] Along with RAPTA-C, RAPTA-T exerts anti-metastatic activity and adds another valuable and efficient representative to the family of RAPTA compounds.…”
Section: Properties Of Rapta Compoundsmentioning
confidence: 99%
“…[100][101][102] Several studies describe the use of RAPTA-C in combination with other drugs. [12,13,73,74,78] It appears, especially in in vitro settings, that Ru-based products exceed the efficacy of Pt-based regimens and might provide a better safety profile for prospective clinical use. This effect arises from the blockade of receptor phosphorylation, further inhibiting the activation of the kinase cascade.…”
Section: Side Effectsmentioning
confidence: 99%
“…[2][3][4] Thea cidic patch is vital for folding the nucleosome into chromatin fiber,the repression of transcription and as the docking area for regulatory proteins. [8][9][10][11][12][13][14] RAPTA-T is an antimetastatic drug, with inhibitory properties towards both primary and metastatic tumors, [15,16] and displays strong site selectivity towards the acidic patch at binding sites consisting of carboxylate groups E61 and E64 on H2A (RU1) and imidazole H106 and carboxylate E102 groups on H2B (RU2). [8][9][10][11][12][13][14] RAPTA-T is an antimetastatic drug, with inhibitory properties towards both primary and metastatic tumors, [15,16] and displays strong site selectivity towards the acidic patch at binding sites consisting of carboxylate groups E61 and E64 on H2A (RU1) and imidazole H106 and carboxylate E102 groups on H2B (RU2).…”
mentioning
confidence: 99%
“…[4][5][6][7] Thea cidic patch plays host to at least two specific metal binding sites belonging to RAPTA-T,[ h 6 -p-toluene)Ru(1,3,5-triaza-7phosphaadamantane)Cl 2 ] ( Figure 1), and auranofin, [(3,4,5triacetyloxy-6-acteyloxymethyl,oxane-2-thio-late)Au(triethylphosphanium)] (AUF, Figure 1). [13] TheR U1 and RU2s ites have been crosslinked by binuclear RAPTA-like complexes linked via the arene using av ariety of rigid and flexible linkers that strongly influence the nature of the crosslink. [13] TheR U1 and RU2s ites have been crosslinked by binuclear RAPTA-like complexes linked via the arene using av ariety of rigid and flexible linkers that strongly influence the nature of the crosslink.…”
mentioning
confidence: 99%